Aphthous lesions turned out to be neonatal very early-onset inflammatory bowel disease: a case report - Hutmacher, Felix; Doerig, Selina; Grobholz, Rainer; Köhler, Henrik; Meyer, Philipp; Baumann, Philipp (Frontiers in Pediatrics, 2024)
Neonatal diagnosis of inflammatory bowel disease (IBD) proves challenging due to its non-specific symptoms. A term-born neonate showing states of inflammation and aphthae was treated for sepsis and candidiasis before being diagnosed with interleukin-10 receptor deficiency and consecutive IBD. The patient was finally successfully treated by stem cell transplantation. The case illustrates the difficulties of the diagnostic course in IBD as it may mimic other diseases and emphasizes the importance of considering rare differential diagnoses early in the diagnostic process.